Мотивація вивчення іноземної мови як соціальна функція освіти - Гончаренко, Тетяна Євгенівна (НТУ "ХПI", 2010)
The paper deals with the factors of motivation while studying English for Specific Purposes (ESP). A new approach of maintaining students’ knowledge on ESP at а proper level is shown.
Keywords: мотивація; психологічна якість; соціальна функція освіти